Aggregate and slag cement effects on autogenous shrinkage in cementitious materials. (15th September 2016) - Liu, Zhichao; Hansen, Will
Highlights: Autogenous shrinkage is calculated by removing the thermal effects associated with cement hydration. Aggregate content effect is studied by an improved Pickett's model. Slag cement effect is characterized by a scaling method. Partial replacement with LWA is used to effectively mitigate autogenous shrinkage. Abstract: This study investigates the susceptibility of cementitious materials to internal moisture condition by the autogenous deformation measurement in the 0.35 water-binder (w/b) ratio systems (paste, mortar and concrete). Autogenous shrinkage is obtained by separating the thermal effects from the measured total deformation using the maturity concept and the coefficient of thermal deformation (CTD). Three factors affecting the autogenous shrinkage are presented, that is the aggregate content, the partial replacement of portland cement with slag cement and of normal weight fine aggregate with lightweight aggregate (LWA). Autogenous shrinkage is clearly reduced by an increasing aggregate content and this effect is predicted by an improved Pickett's model using a time-dependent aggregate restraining factor. A binary cementitious system of portland cement and slag cement increases the autogenous shrinkage in the long term. Contribution of slag cement can be characterized by the difference in autogenous shrinkage between the binary system and the control system scaled down by the replacement ratio. The negative effect of slag cement can be neutralized by the incorporation of LWA as a partial sand replacement.